Kewajiban Atas Divestasi Saham Bidang Pertambangan Minerba Di Indonesia Dalam Perspektif Keadilan - Suradiyanto Suradiyanto (Law Department, University of Widya Gama Mahakam Samarinda, 2019)
The potential of natural resources owned by Indonesia need to be processed in order to make a significant contribution to the economy of the country which ultimately intended for the welfare of the people. One of the natural resources that have economic value that is large enough is mineral resources and coal, but without the management of the potential of natural resources will not mean anything. Dynamics faced by Indonesia as a developing country, faced with a number of internal problems including the limitations of technology, sources of funds and human resources. These things are the constraints in the management and utilization of natural resources by the state. To overcome these obstacles, the Indonesian government to cooperate with investors in the management of existing natural resources contained in a concept of cooperation known as Contract of Work. The development that occurs in Mining Law the existence of divestment obligations as a requirement in a Contract of Work.